Select human cancer mutants of NRMT1 alter its catalytic activity and decrease N‐terminal trimethylation. (11th June 2017) - Shields, Kaitlyn M.; Tooley, John G.; Petkowski, Janusz J.; Wilkey, Daniel W.; Garbett, Nichola C.; Merchant, Michael L.; Cheng, Alan; Schaner Tooley, Christine E.
Abstract: A subset of B‐cell lymphoma patients have dominant mutations in the histone H3 lysine 27 (H3K27) methyltransferase EZH2, which change it from a monomethylase to a trimethylase. These mutations occur in aromatic resides surrounding the active site and increase growth and alter transcription. We study the N‐terminal trimethylase NRMT1 and the N‐terminal monomethylase NRMT2. They are 50% identical, but differ in key aromatic residues in their active site. Given how these residues affect EZH2 activity, we tested whether they are responsible for the distinct catalytic activities of NRMT1/2. Additionally, NRMT1 acts as a tumor suppressor in breast cancer cells. Its loss promotes oncogenic phenotypes but sensitizes cells to DNA damage. Mutations of NRMT1 naturally occur in human cancers, and we tested a select group for altered activity. While directed mutation of the aromatic residues had minimal catalytic effect, NRMT1 mutants N209I (endometrial cancer) and P211S (lung cancer) displayed decreased trimethylase and increased monomethylase/dimethylase activity. Both mutations are located in the peptide‐binding channel and indicate a second structural region impacting enzyme specificity. The NRMT1 mutants demonstrated a slower rate of trimethylation and a requirement for higher substrate concentration. Expression of the mutants in wild type NRMT backgrounds showed no change in N‐terminal methylation levels or growth rates, demonstrating they are not acting as dominant negatives. Expression of the mutants in cells lacking endogenous NRMT1 resulted in minimal accumulation of N‐terminal trimethylation, indicating homozygosity could help drive oncogenesis or serve as a marker for sensitivity to DNA damaging chemotherapeutics or γ‐irradiation.